A NAC‐type transcription factor confers aluminium resistance by regulating cell wall‐associated receptor kinase 1 and cell wall pectin. (2nd December 2019) - Lou, He Qiang; Fan, Wei; Jin, Jian Feng; Xu, Jia Meng; Chen, Wei Wei; Yang, Jian Li; Zheng, Shao Jian
Abstract: Transcriptional regulation is important for plants to respond to toxic effects of aluminium (Al). However, our current knowledge to these events is confined to a few transcription factors. Here, we functionally characterized a rice bean ( Vigna umbellata ) NAC‐type transcription factor, VuNAR1, in terms of Al stress response. We demonstrated that rice bean VuNAR1 is a nuclear‐localized transcriptional activator, whose expression was specifically upregulated by Al in roots but not in shoot. VuNAR1 overexpressing Arabidopsis plants exhibit improved Al resistance via Al exclusion. However, VuNAR1‐mediated Al exclusion is independent of the function of known Al‐resistant genes. Comparative transcriptomic analysis revealed that VuNAR1 specifically regulates the expression of genes associated with protein phosphorylation and cell wall modification in Arabidopsis . Transient expression assay demonstrated the direct transcriptional activation of cell wall‐associated receptor kinase 1 ( WAK1 ) by VuNAR1. Moreover, yeast one‐hybrid assays and MEME motif searches identified a new VuNAR1‐specific binding motif in the promoter of WAK1 . Compared with wild‐type Arabidopsis plants, VuNAR1 overexpressing plants have higher WAK1 expression and less pectin content. Taken together, our results suggest that VuNAR1 regulates Al resistance by regulating cell wall pectin metabolism via directly binding to the promoter of WAK1 and induce its expression. Abstract : A rice bean NAC‐type transcription factor is involved in Al resistance by directly regulating WAK1 expression that is associated with cell wall pectin content.